Municipal Public-Private Partnership Framework - World Bank (World Bank, Washington, DC, 2020)
Municipal governments and staff are seeking to implement public-private partnerships (PPPs) to help meet their infrastructure development needs. This framework is modular, comprising a guidance note, 20 topic guidance on key issues, and a collection of project summaries that highlight innovative approaches to municipal PPP around the world.